Dimensions of National Security and Development of Nepal - Paudel, Ramesh Raj (Unity Journal, 2021)
The dimensions of national security are increasing in the world day by day. In a similar fashion, development is also becoming a multi-perspective phenomenon. However, both of them differ from country to country. Therefore, it needs a better understanding of the country-specific scenarios. The scenario of Nepal is also a specific subject matter in this regard because of its own inherent multidimensional features related to its geography, economy, sociocultural aspects, environmental aspects, and others. This study aims to explore the key dimensions of national security, key perspectives of development, and the two-way interrelation between national security and the development of Nepal. More specifically, this study focuses on the following research questions in the context of Nepal: What are the key dimensions of national security? What are the key perspectives of development? How dimensions of national security and perspectives of development interrelate to each other? This is qualitative research, and uses secondary information through books, journal articles, newspaper articles, magazines, and others. Moreover, I come up with some resolutions to the issue of national security through discursive practices and critical analysis Three conclusive points of the study are: (i) As a buff er state, the concentration of national security lies on its border and culture whereas as a member of the globe the concentration lies on its economy, politics, environment, and information technology. (ii) Common perspectives of development in the recent world are generally applicable in the case of Nepal. (iii) Political, economic, sociocultural, environmental, human, and information technological domains of interrelation are applicable in the context of Nepal.